Pendampingan Aplikasi Sorogan Kitab Jawi di Majlis Ta’lim Baetul Wasilah Desa Sindangpanon Kecamatan Bojong Purwakarta: (Aplikasi Sorogan Kitab Jawi di Majlis Ta’lim Baetul Wasilah Desa Sindangpanon, Bojong, Purwakarta, Jawa Barat) - Kania, Irna; Supendi, Dede (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The research was carried out during a pandemic so that teaching and learning activities were carried out online, this resulted in children, especially at elementary school age, tending to overuse gadgets. Apart from that, it also effects the recitation lesson. Effort to reduce excessive use of gadgets are carried out in the form of applications to recite books through community service activies.Action research methods used with Participatory Action Research (PAR) design. Starting with looking at the problem, interpreting and analyzing it, then action/ action is carried out as an alleviation of existing problems. Based on these actions gradually underwent changes, where children began to reduce their use on gadgets. In addition, they can take the time to start target inthe recitation lesson,starting with understanding the book that will be read through sorogan and hopefully in the future it can have a positive impact on other lessons such asmemorization.